PERAN ORANG TUA TENTANG ERUPSI GIGI GERAHAM PERTAMA PERMANEN DENGAN PREVALENSI KARIES GIGI GERAHAM PERTAMA PERMANEN - Silvia Prasetyowati; Nur Fitri Febriasari; Ni Ketut Nuratni (Jurnal Kesehatan Gigi (Dental Health Journal), 2020)
Backgrounds : The most people still faces problem of cavities or caries. School age children is one of vulnerable to caries, because most still have knowledge and behavior that less against dental caries. The first molar permanent teeth are the most commonly carious teeth in children and teenagers. Problems in this study is the high prevalence of caries on the molar teeth first permanent students class I-VI at SDN Mojo III Surabaya in 2019. Objective : To analyze the relationship between the role of parents about first molar permanent eruption with prevalence caries first molar permanent students class I-VI at SDN Mojo III Surabaya in 2019. Methods : This research used analytical survey method with cross sectional approach, it means the study analyzed the relationship between variable without the treatment by researcher. The total Error! Reference source not found.number of the research is 87 students. Instrument used in this research was questionnaire to knowing the role of parents and to kowing caries of first molar permanent using the sheets. Technique of data analysis using SPSS program with Chi-Square test. Conclusion : There is correlation between the role of parents about first molar permanent eruption with prevalence caries first molar permanent students class I-VI at SDN Mojo III Surabaya in 2019